2016
DOI: 10.2174/1381612822666160905123953
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Ecosystem Disruption in Autism Spectrum Disorder: Can the Microbiota and Macrobiota be Restored?

Abstract: If these theoretical models prove to be valid, they may lead to the development of practical interventions which could decrease ASD prevalence and/or morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 208 publications
(255 reference statements)
0
26
0
1
Order By: Relevance
“…The enteric microbiome, a diverse ecosystem of bacteria, fungi, viruses and their collective genomes, resides in the GI tract and aids in vitamin synthesis, immune regulation and host metabolism [12]. Folate is synthesized by enteric bacterial species, particularly Bifidobacteria, Prevotella and certain Lactobacilli species [13][14][15][16][17].…”
Section: The Importance Of the Microbiome And Folate Transporters In Fomentioning
confidence: 99%
See 1 more Smart Citation
“…The enteric microbiome, a diverse ecosystem of bacteria, fungi, viruses and their collective genomes, resides in the GI tract and aids in vitamin synthesis, immune regulation and host metabolism [12]. Folate is synthesized by enteric bacterial species, particularly Bifidobacteria, Prevotella and certain Lactobacilli species [13][14][15][16][17].…”
Section: The Importance Of the Microbiome And Folate Transporters In Fomentioning
confidence: 99%
“…The notion that disruption of folate metabolism during gestation could contribute to ASD is supported by two epidemiological studies which demonstrated that folate supplementation during the preconception period as well as pregnancy was protective of offspring from developing ASD or NTD [51,52]. It has also been suggested that maternal microbiome disruption during pregnancy could also contribute to abnormal folate metabolism during pregnancy and be associated with ASD development [12]. The connection between FRAAs during pregnancy and ASD is supported by a recent rodent model developed in the Quadros laboratory.…”
Section: Effect Of Fraas In Pregnancymentioning
confidence: 99%
“…The groups of MacFabe and Frye have published extensively on the potential importance of propionic acid including its use as a food preservative . There is evidence that increased propionate could result from changes in the microbiome which in turn relates to gastrointestinal disorders and mitochondrial function . At least four reviews of the relevance of the microbiome to autism appeared in 2016 , and the potential for interaction with brain carnitine deficiency could be substantial.…”
Section: Mitochondrial Abnormalities Generally In Autismmentioning
confidence: 99%
“…Therefore, most of such conditions represent the consequence of interaction between individual's genetic profile and the environment that he/she is exposed to (Blatt, ). Emerging research has shown microbiota and their metabolites dynamically affect host metabolic, immune, behavioural processes and gut‐brain communications throughout the lifecycle (Bilbo, Block, Bolton, Hanamsagar, & Tran, ; Kim, Yun, Oh, & Choi, ; MacFabe, ; Sharon et al, ; Shenderov & Midtvedt, ; Slattery, MacFabe, Kahler, & Frye, ;). The relationship between gastrointestinal symptoms and many neurological states, such as anxiety, depression, stress and ASD is shown in numerous studies (Foster, Rinaman, & Cryan, ; Fung, Olson, & Hsiao, ; Ishii et al, ).…”
Section: Introductionmentioning
confidence: 99%